Recriar o espaço de voz do poeta: a memória entre dois mundos - Joseilda de Sousa Diniz (Universidade de Brasília, 2010)
Poet, singer, reciter, engraver, who, after a tragic illness in the vocal cords became a researcher and a writer, José Alves Sobrinho was one of the main nomad poetsingers on Northeast Brazil. His name is linked to a period deemed the golden age of Brazilian cantoria and brings a privileged testimony of this effervescent moment, marked by the transition to new technologies of information. Deeply embedded in these changing times, where the sung word loses progressively space to the printed one, José Alves knew, cleverly, recreate a space of dialogue between the letter and the poem. Following his intellectual and artistic trajectory, we can realize the creative ability of this poet and his pears, in the sense of recreating the needed possibilities to the maintenance, spreading, adaptation and survival of his art.